The effect of carbonyl amide substituents on the conductivity and thermal stability of cmc-thiourea polymer electrolytes - Saidatul Radhiah Ghazali (Terengganu: Universiti Malaysia Terengganu, 2014)
For the past few decades, thiourea has attracted great attention to be developed in numerous applications. The linear conjugated thiourea system provides wide range of electronic properties as they consist of rigid π-systems on their structures. This study covered two main phases. The first phase is the synthetic work and characterization of alkoxy thiourea derivatives. The second phase is the preparation and characterization of complexes (CMC-thiourea) as polymer electrolytes.